Uji Bioaktivitas Antibakteri Ekstrak Kayu Akar Bayur (Pterospermum subpeltatum C.B.Rob) - Pince Salempa; Alfian Noor; Nunuk Hariani; Tjodi Harlim (Bionature, 2009)
Pterospermum subpeltatum C.B. Rob or bayur is traditionally and widely used as medicine for infection diseases caused by bacteria. Four extract from root stem of this plant were evaluated for their antibacterial activity properties against Escherichia coli, Shigella boydii, staphylococcus aureus danStreptococcus mutan. All the extract were able to inhibited the bacterial strain except Staphylococcus aureus. Chloroform extract exhibited effect for Shigella boydii and Streptococcus mutan. Hexana extract for Escherichia coli, while methanol extract for Shigella boydii. All extract showed an effect at the same extend (MIC; 50 mg/ml).